Behavioral Health Services for Women Who Have Breast Cancer - Azzone, Vanessa (American Society of Clinical Oncology, 2009)
PURPOSE: To explore whether the use of behavioral health services (BHS) among women with breast cancer is influenced by how insurance plans administer these services, we compared utilization of psychotherapy and psychotherapeutic medications among women with breast cancer who received BHS coverage through a carve-out versus integrated arrangement. PATIENTS AND METHODS: We analyzed insurance claims, enrollment data, and benefit design data from the MarketScan Commercial Claims & Encounters Research Database for the years 1998 to 2002 for women ≤ 63 years old with newly diagnosed breast cancer. We compared the probability of receiving psychotherapy, the likelihood of receiving antidepressant/antianxiety/hypnotic medications, and the number of psychotherapy sessions used during the year after a breast cancer diagnosis among women whose behavioral health services were provided through carve-out versus integrated arrangements. RESULTS: Women enrolled in carve-outs were significantly less likely to receive any psychotherapy visits compared with women in integrated arrangements (odds ratio, 0.68; P < .01). Conditional on having received psychotherapy, however, women in carve-out arrangements used more psychotherapy visits than women in integrated arrangements. The use of antianxiety/hypnotic drugs was significantly higher for women in carve-out arrangements versus women in integrated arrangements (36.1% v 32.6%, P < .05). Moreover, women who received psychotherapy were significantly more likely to received antidepressants and antianxiety/hypnotic medications (five and three times more likely, respectively). CONCLUSION: The type of BHS arrangement was associated with the utilization of psychotherapy and psychotherapeutic medications among women with breast cancer.